Advanced Ultrasound Application – Impact on Presurgical Risk Stratification of the Thyroid Nodules - Stoian D; Ivan V; Sporea I; Florian V; Mozos I; Navolan D; Nemescu D (Dove Medical Press, 2020)
Dana Stoian, 1, 2 Viviana Ivan, 1 Ioan Sporea, 1 Varcus Florian, 3 Ioana Mozos, 4 Dan Navolan, 5 Dragos Nemescu 6 1 2nd Department of Internal Medicine, “Victor Babes” University of Medicine, Timisoara, Romania; 2Dr. D Center for Ultrasound in Endocrinology, Timisoara, Romania; 3 2nd Department of Surgery, “Victor Babes” University of Medicine, Timisoara, Romania; 4Department of Physiopathology, “Victor Babes” University of Medicine, Timisoara, Romania; 5Department of Obstetrics Gynecology, “Victor Babes” University of Medicine, Timisoara, Romania; 6Department of Obstetrics Gynecology, “Gr. T. Popa” University of Medicine, Iasi, RomaniaCorrespondence: Dan NavolanDepartment of Obstetrics Gynecology, “Victor Babes” University of Medicine and Pharmacy Timisoara, P-ta Eftimie Murgu, Nr. 2, Timisoara 300011, RomaniaEmail navolan@yahoo.comViviana Ivan 2nd Department of Internal Medicine, “Victor Babes” University of Medicine and Pharmacy Timisoara, P-ta Eftimie Murgu, Nr. 2, Timisoara 300011, RomaniaTel +40 722 960 911Fax +40 256 020 1890Email ivanmvivi@yahoo.comAim: Current major guidelines recommend risk stratification of the thyroid nodules, after each diagnostic evaluation, in order to focus attention on potentially risky nodules. The main aim of our study was to evaluate the performance of combined advanced ultrasound techniques in this process, compared with conventional stratification models, in order to reduce unnecessary fine-needle biopsies, respectively, surgery.Material and Methods: We evaluated 261 cases (261 nodules) using conventional ultrasound (2B), real-time Doppler evaluation (4D) respectively, real-time elastography, using a linear multifrequency probe and a linear volumetric probe (Hitachi Prerius Machine, Hitachi Inc, Japan). All the nodules were classified using a risk stratification model comprising seven conventional US characteristics, two 4 D characteristics and a color map RTE aspect. The results were compared with the pathology results, considered the golden standard diagnosis.Results: The prevalence of malignant nodules was 21.83% (57 cases). Conventional risk classification generated: 106 low-risk cases, 113 intermediate-risk and 42 high-risk cases. Our proposed risk classification changes the conventional risk classification with a risk upgrade in 27 cases and with a risk downgrade in 69 cases. The diagnostic quality of the combined risk stratification model was better, considering a low-risk category predictive for benignancy and a high category predictive for malignancy: Sensitivity: 80.88% versus 49.01%, respectively, Specificity: 91.22% versus 54.38. The diagnostic power differences were observed regardless of the nodule size.Conclusion: Advanced ultrasound techniques did add diagnostic value in the presurgical risk assessment of the thyroid nodules.Keywords: strain elastography, volumetric Doppler, complex ultrasound thyroid evaluation, risk stratification